2017
DOI: 10.1016/j.bpj.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Charge, Diffusion, and Current Fluctuations of Single-Stranded DNA Trapped in an MspA Nanopore

Abstract: We report effective charges and diffusion constants of several different single-stranded DNA oligonucleotides trapped in an MspA nanopore. Nucleotide identity is found to have a substantial influence on effective charges and diffusion constants. These quantities are determined from escape time experiments for a DNA molecule attached to a NeutrAvidin molecule that, unlike the DNA, does not pass through the pore. Correlations are reported between oligonucleotide effective charges and current blockages, and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It should be noted that even a quantity as commonplace as a diffusion constant can be observed to change dramatically in the context of a periodic attractive potential [20, 61]. Indeed, the values observed here, while quite reasonable, are significantly smaller than those reported for ssDNA in the MspA channel in the context of a simplified energy landscape model [62].…”
Section: Discussionmentioning
confidence: 47%
“…It should be noted that even a quantity as commonplace as a diffusion constant can be observed to change dramatically in the context of a periodic attractive potential [20, 61]. Indeed, the values observed here, while quite reasonable, are significantly smaller than those reported for ssDNA in the MspA channel in the context of a simplified energy landscape model [62].…”
Section: Discussionmentioning
confidence: 47%
“…Dividing eq by eq , we obtain where ε 0 is the permittivity of free space. The zeta potential ζ and relative permittivity of filter paper ε r are 20 mV and 80, respectively, and the effective charge of ssDNA133a is 1.936 –18 C (determined using the effective charge of single base of ssDNA Q eff = 0.55e – , base size r 0 = 0.34 nm, and the number of bases n = 22). By substituting the above-mentioned number into eq , it can be seen that v ep is around 12 times higher than v eof , indicating that v ep is the dominant behavior and ssDNA is thus continuously transported from the cathodic side to the anodic side.…”
Section: Resultsmentioning
confidence: 99%
“…The results have demonstrated that the engineered MspA has a single-base resolution and can distinguish four different bases comparable to α-HL . Subsequently, it has been widely used to investigate single-oligonucleotide analysis, methylcytosine detection, and even natural DNA sequencing. ,, …”
Section: Biosensing Platforms Derived From Mdsmentioning
confidence: 99%